1984
DOI: 10.1159/000275691
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stapedial Reflex in Neuromuscular Diseases

Abstract: An impedance audiometric analysis of the stapedial reflex was carried out in 17 patients with motor neuron disease (MND), 11 with myasthenia gravis (MG), and 3 myotonic dystrophy (MD). The features examined were the threshold and latency parameters and the response pattern of the reflex. All groups had mean reflex thresholds within normal limits (80–90 dB hearing level). The MND group showed a lengthened mean reflex latency (L1). The MG group showed an unstable response pattern to 10-second tone sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Smirne et al [25] and Zakrisson et al [29] found significantly prolonged relaxation time (D 50 ) in DM patients. Yamane et al [28], who studied three reflex measures (L, C 50 and D 50 ) in three DM patients, reported that L and D 50 were significantly longer than in the control subjects and that C 50 was longer but not statistically significantly so (500 Hz stimuli). In contrast, Huygen et al [9], who performed auditory function tests on 13 DM patients, found that D 50 was normal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Smirne et al [25] and Zakrisson et al [29] found significantly prolonged relaxation time (D 50 ) in DM patients. Yamane et al [28], who studied three reflex measures (L, C 50 and D 50 ) in three DM patients, reported that L and D 50 were significantly longer than in the control subjects and that C 50 was longer but not statistically significantly so (500 Hz stimuli). In contrast, Huygen et al [9], who performed auditory function tests on 13 DM patients, found that D 50 was normal.…”
Section: Discussionmentioning
confidence: 95%
“…The stapedial reflex therefore can be used to show muscle weakness and myotonia separately in the stapedial muscle. Several reports have been published on the stapedial reflex in patients with myotonic dystrophy (DM) [9,25,28,29]. Smirne et al [25] and Zakrisson et al [29] found significantly prolonged relaxation time (D 50 ) in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the reflex threshold in PD was slight and the significance of the decline is indefinite. A prolongation of C50 or a similar parameter was reported in spastic dysphonia [7] and multiple sclerosis [2,[10][11][12], and a prolon gation of D50 or a similar parameter was reported in mul tiple sclerosis [2 ], myotonic dystrophy [1], progressive muscular dystrophy [4], sensorineural hearing loss [ 13], and spasmodic dysphonia [14], But, these results are par tially controversial.…”
Section: Discussionmentioning
confidence: 95%
“…Stapedial reflex (SR) has been investigated in various neurological diseases using impedance audiometry [1][2][3][4][5][6][7], Parkinson's disease (PD) is a neurological disease charac terized by muscle rigidity, tremor, and akinesia. Abnor malities of the stretch reflex [8 ] and the blink reflex [9] in PD have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…If a diagnosis of MG is suspected, it can be confirmed using in unologic, pharmacological, and electrophysiologic testing [6,11,12]. Additional noninvasive testing, such as stapedius reflex testing, is advocated as a means to identify and further differentiate neuromuscular diseases such as MG [15][16][17].…”
Section: Discussionmentioning
confidence: 99%